Ultrahigh-viscosity PBT material and preparation method thereof

By introducing the reaction of aromatic homotriamine and trihydroxy triacrylate into PBT materials, as well as the use of ion capping and modifiers, a multifunctional structure is formed, which solves the degradation of performance and bonding properties of traditional PBT materials at high temperatures. The problem of insufficient results has achieved significant improvements in the high viscosity, cohesion and mechanical properties of the material.

CN119306957AInactive Publication Date: 2025-01-14浙江长鸿生物材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411865328.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional PBT materials have degraded performance in high-temperature environments, insufficient adhesive properties and chemical stability, which limits their use in high-end applications.

Method used

By reacting aromatic homotriamine and trihydroxy triacrylate in an organic solvent, a hyperbranched polymer is formed, and an ionic blocking agent and a modifier are added to form a multifunctional structure, which enhances the interaction force and intersection between molecules. Connection density to improve the viscosity, cohesion and mechanical properties of the material.

Benefits of technology

It significantly improves the viscosity, cohesion, mechanical strength and heat resistance of PBT materials, enhances the adhesive properties and chemical stability, and meets the needs of high-end applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of an ultrahigh-viscosity PBT (Polybutylene Terephthalate) material, which comprises the following steps: S1, reacting aromatic s-triamine with trihydroxy triacrylate and olefine acid under a certain condition to obtain a hyperbranched polymer; s2, reacting the hyperbranched polymer with an ion end-capping reagent to obtain an ion-terminated hyperbranched polymer; s3, PBT resin is added into a mixed solution formed by compounding short-chain alcohol and strong base for an alcoholysis reaction, then a modifier formed by compounding glycidol and choline is added for a reaction with the PBT resin alcoholysis product, and polyfunctional group modified PBT resin is obtained; and S4, carrying out melt blending, extrusion and granulation on the ion-terminated hyperbranched polymer and the polyfunctional group modified PBT resin to obtain the ultrahigh-viscosity PBT material. According to the preparation method, the ultrahigh viscosity performance of the PBT material is achieved, the overall comprehensive performance of the material is optimized, and meanwhile it is guaranteed that the processability of the PBT material can meet the requirements of the high-end application field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of PBT materials, and in particular to an ultra-high viscosity PBT material and a preparation method thereof. Background Art

[0002] In the field of engineering plastics, polybutylene terephthalate (PBT) is widely used in electronics, automobiles, aerospace and other industries due to its excellent comprehensive properties. PBT materials are favored for their good mechanical properties, heat resistance, chemical resistance and processing convenience. However, traditional PBT materials still have performance deficiencies in some high-end applications, especially in situations where higher viscosity, stronger cohesion and better mechanical properties are required. For example, under high temperature conditions, traditional PBT materials may not be able to maintain their performance, resulting in component failure. In addition, traditional PBT materials also have limitations in bonding performance and chemical stability, which restricts their application in more severe environments. Therefore, the industry has been seeking to improve the performance of PBT materials through modification to meet the growing demand for high-performance engineering plastics. Although some improvement methods have been proposed, these methods often fail to fully solve the above problems and may introduce new process complexities and increased costs. Summary of the invention

[0003] In view of the above shortcomings of the prior art, the present invention provides a method for preparing an ultra-high viscosity PBT material to solve the shortcomings of traditional PBT materials in that they cannot have both high viscosity and high mechanical properties and heat resistance, thereby achieving a significant improvement in performance.

[0004] To achieve the above purpose, the technical solution adopted by the present invention is: a method for preparing an ultra-high viscosity PBT material, the preparation method comprising the following steps: S1: dissolving an aromatic homotriamine and trihydroxy triacrylate in an organic solvent respectively, and adding a trihydroxy triacrylate solution and an olefinic acid dropwise to the aromatic homotriamine solution at 15 to 30° C. and in a nitrogen atmosphere. After the addition is completed, the temperature is raised to 85 to 95° C. for reflux reaction, and then vacuum distillation is performed to obtain a hyperbranched polymer; in the preparation method of the PBT material of the present invention, in step S1, the olefinic acid has a bifunctional structural characteristic, one end of which contains a carboxyl group and the other end of which contains an olefin unsaturated double bond. The carboxyl group of the olefinic acid reacts with the primary amine group of the aromatic homotriamine to form an amide bond. This reaction not only constructs an important connection point in the polymer molecular chain, but also greatly enhances the interaction force between molecules through the formation of an amide bond, thereby significantly improving the overall cohesion and viscosity of the PBT material. At the same time, the unsaturated double bonds of olefinic acid are used to react with trihydroxy triacrylate to further expand the branched structure of the polymer and enhance the cross-linking density of the material.

[0005] S2: dissolving the hyperbranched polymer obtained in step S1 in an organic solvent, adding an ionic end-capping agent, heating and sealing the reaction for a certain period of time, and obtaining an ionic end-capped hyperbranched polymer after reduced pressure distillation; in step S2, by reacting the hyperbranched polymer with the ionic end-capping agent, the end of the polymer chain is charged, the electrostatic interaction between molecules is enhanced, and the cohesion of the polymer network is improved. The introduction of this charge not only promotes the attraction between molecules, but also helps to form an ionic cross-linked network, increasing the adhesion and overall viscosity of the material. At the same time, due to the change in surface properties, the polymer after ionic end-capping improves the compatibility with other polymers or additives, improves the processing performance of the material, makes it easier to process into the desired shape and product, and meets the needs of industrial production. In addition to significantly improving the viscosity and cohesion of the PBT material, the ionic end-capped hyperbranched polymer prepared by the present invention also enhances the mechanical strength and heat resistance of the material.

[0006] S3: PBT resin is added to a mixed solution of short-chain alcohol and strong base, and the temperature is raised for alcoholysis reaction. After the reaction is completed, the alcohol of unreacted substances and the generated low-molecular alcohol are purified and removed, and a modifier compounded by propylene oxide and choline is added to react with the alcoholysis product of the PBT resin to obtain a multifunctional modified PBT resin; in step S3 of the present invention, by adding PBT resin to a mixed solution of short-chain alcohol and strong base for alcoholysis reaction, and introducing a modifier compounded by propylene oxide and choline, not only the viscosity of the PBT material is significantly improved due to the introduced epoxy group, but also the quaternary ammonium salt structure introduced by choline promotes the formation of an ion cross-linking network, and further improves the cohesion and overall performance of the PBT resin by enhancing the electrostatic interaction between molecules. This modified PBT resin not only exhibits better bonding performance and meets the application requirements of high bonding performance, but also exhibits better thermal stability and mechanical properties due to the enhanced intermolecular forces and ion cross-linking network during high-temperature processing, which helps to maintain the viscosity and morphology of the material during processing.

[0007] S4: adding the ion-terminated hyperbranched polymer obtained in step S2 and the multifunctional modified PBT resin obtained in step S3 into a twin-screw extruder for full melt blending, and then extruding, cooling, granulating, drying and packaging to obtain the ultra-high viscosity PBT material.

[0008] As a preferred technical solution, the aromatic homotriamine is at least one of melem, melamine, 1,5,9-benzotriamine, and tri(4-aminophenyl)amine. The introduction of the aromatic homotriamine of the present invention, due to its stable aromatic ring structure, enhances the π-π stacking effect and conjugation effect between molecules, which not only improves the interaction force between molecules, improves the cohesion and overall performance of the material, but also increases the thermal stability of the material, so that it maintains performance under high temperature processing and application environments. In addition, the addition of aromatic homotriamine increases the rigidity of the polymer chain and improves the mechanical properties of the PBT material, such as tensile strength and modulus. The reactivity of the amino group in the aromatic structure with the olefinic acid is improved, which helps to form a stable hyperbranched structure, while enhancing the chemical resistance and aging resistance of the material and extending the service life of the material.

[0009] As a preferred technical solution, the trihydroxy triacrylate is at least one of trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), and glycerol trihydroxypropyl ether triacrylate. The addition of trihydroxy triacrylate in the present invention, on the one hand, enhances the cross-linking ability of the PBT material, and forms a three-dimensional network structure with a hyperbranched structure through the participation of its acrylate group in polymerization and cross-linking reactions, thereby improving the cohesion and mechanical strength of the material; on the other hand, the introduction of the acrylate group significantly improves the bonding performance of the material, and forms new chemical bonds by reacting with functional groups on other monomers or polymer chains, thereby enhancing the bonding strength. At the same time, the introduction of the acrylate group also improves the processing properties of the material, such as fluidity and formability, improves production efficiency and product quality, and enhances optical properties, such as transparency and gloss, to meet the needs of high optical performance applications.

[0010] As a preferred technical solution, the olefinic acid is at least one of acrylic acid, methacrylic acid and crotonic acid.

[0011] As a preferred technical solution, the molar ratio of the aromatic triamine, trihydroxy triacrylate and olefinic acid is 1:1-1.5:1-1.5.

[0012] As a preferred technical solution, the ionic capping agent is at least one of olefin hydrochloride, olefin sulfonate or olefin phosphate.

[0013] As a preferred technical solution, the short-chain alcohol is at least one of methanol, ethanol, isopropanol and butanol.

[0014] As a preferred technical solution, the strong base is at least one of sodium hydroxide, potassium hydroxide and potassium carbonate.

[0015] Another aspect of the present invention is to provide an ultra-high viscosity PBT material, wherein the PBT material is prepared by the above-mentioned method for preparing the ultra-high viscosity PBT material.

[0016] As a preferred technical solution, the intrinsic viscosity of the PBT material is 1.3-1.5 dL / g.

[0017] Beneficial effects of the present invention: The preparation method of the ultra-high viscosity PBT material of the present invention not only realizes a significant improvement in the ultra-high viscosity of the PBT material, but also optimizes the overall comprehensive performance of the material by innovatively introducing a specific chemical modification step and a precisely controlled polymerization reaction. This design not only enhances the cohesion and mechanical properties of the PBT material, but also maintains the processability and flexibility of the material, which helps to expand its scope of use in high-end application fields.

[0018] In general, the ultra-high viscosity PBT material of the present invention not only has excellent mechanical properties and heat resistance, but also exhibits excellent bonding properties and chemical stability, which can meet the stringent requirements of modern industry for high-performance engineering plastics, especially in key applications such as electronics, automobiles, and aerospace that require long-term durability and stability. DETAILED DESCRIPTION

[0019] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0020] Example 1, S1: Melem and trimethylolpropane triacrylate are respectively dissolved in an organic solvent, dimethyl sulfoxide. At 25° C. and in a nitrogen atmosphere, trimethylolpropane triacrylate solution and acrylic acid are added dropwise to the melem solution, wherein the molar ratio of melem to trimethylolpropane triacrylate and acrylic acid is 1:1:1.5. After the addition is completed, the temperature is raised to 95° C. and refluxed for 2 hours, and then distilled under reduced pressure to obtain a hyperbranched polymer.

[0021] S2: 30 g of the hyperbranched polymer obtained in step S1 was dissolved in 200 ml of dimethyl sulfoxide, an organic solvent, 1% olefin hydrochloride was added (based on the weight percentage of the polymer), the temperature was raised to 60° C. and the reaction was carried out in a sealed manner for 3 hours, and the ion-terminated hyperbranched polymer was obtained after distillation under reduced pressure.

[0022] S3: Add 20 grams of PBT resin into a mixed solution of ethanol and sodium hydroxide, wherein the mass ratio of ethanol to sodium hydroxide is 10:3, and the total volume of the mixed solution is 200 milliliters. Heat to 90°C for alcoholysis reaction for 2 hours. After the reaction is completed, purify and remove the unreacted alcohol and the generated low-molecular alcohol, and then add a modifier prepared by propylene oxide and choline (the molar ratio of propylene oxide to choline is 2:1) to react with the alcoholysis product of the PBT resin. The amount of the modifier added is 5% of the weight of the PBT resin. The reaction temperature is 70°C and the time is 1.5 hours to obtain a multi-functional modified PBT resin.

[0023] S4: The ion-terminated hyperbranched polymer obtained in step S2 and the multifunctional modified PBT resin obtained in step S3 are added to a twin-screw extruder at a weight ratio of 1:4 for full melt blending, the screw speed of the extruder is 300 rpm, the melt temperature is set to 240°C, and the ultra-high viscosity PBT material is obtained by shearing, mixing, extruding, cooling, granulating, drying, and packaging. During the drying process, the material is dried at 60°C for 4 hours to ensure complete removal of moisture.

[0024] The intrinsic viscosity of the PBT material (the same below) was measured by an Ubbelohde viscometer. The intrinsic viscosity of the PBT material in this embodiment was 1.42 dL / g.

[0025] Example 2, S1: Melamine and trimethylolpropane trimethacrylate (TMPTMA) are respectively dissolved in an organic solvent, dimethyl sulfoxide. At 25° C. and in a nitrogen atmosphere, trimethylolpropane trimethacrylate solution and methacrylic acid are dropwise added to the melamine solution, wherein the molar ratio of melamine to trimethylolpropane trimethacrylate and methacrylic acid is 1:1:1.5. After the addition is completed, the temperature is raised to 95° C. and refluxed for reaction for 2 hours, and then distilled under reduced pressure to obtain a hyperbranched polymer.

[0026] S2: 30 g of the hyperbranched polymer obtained in step S1 was dissolved in 200 ml of dimethyl sulfoxide, an organic solvent, 1% of olefin sulfonate was added, the temperature was raised to 60° C. and the mixture was sealed for reaction for 3 hours. After distillation under reduced pressure, an ion-terminated hyperbranched polymer was obtained.

[0027] S3: Add 20 grams of PBT resin into a mixed solution of isopropanol and potassium hydroxide, wherein the mass ratio of isopropanol to potassium hydroxide is 10:3, and the total volume of the mixed solution is 200 milliliters. Heat to 90°C for alcoholysis reaction for 2 hours. After the reaction is completed, purify and remove the unreacted alcohol and the generated low-molecular alcohol, and then add a modifier prepared by propylene oxide and choline (the molar ratio of propylene oxide to choline is 2:1) to react with the alcoholysis product of the PBT resin. The amount of the modifier added is 5% of the weight of the PBT resin. The reaction temperature is 70°C and the time is 1.5 hours to obtain a multi-functional modified PBT resin.

[0028] S4: The ion-terminated hyperbranched polymer obtained in step S2 and the multifunctional modified PBT resin obtained in step S3 are added to a twin-screw extruder at a weight ratio of 1:4 for full melt blending, the screw speed of the extruder is 300 rpm, the melt temperature is set to 240°C, and the ultra-high viscosity PBT material is obtained by shearing, mixing, extruding, cooling, granulating, drying, and packaging. During the drying process, the material is dried at 60°C for 4 hours to ensure complete removal of moisture.

[0029] The intrinsic viscosity of the PBT material described in this embodiment is 1.36 dL / g.

[0030] Example 3, S1: 1,5,9-benzotriamine and glycerol trihydroxypropyl ether triacrylate are respectively dissolved in an organic solvent, dimethyl sulfoxide. At 30° C. and in a nitrogen atmosphere, glycerol trihydroxypropyl ether triacrylate solution and methacrylic acid are added dropwise to the 1,5,9-benzotriamine solution, wherein the molar ratio of 1,5,9-benzotriamine to glycerol trihydroxypropyl ether triacrylate and methacrylic acid is 1:1.2:1.5. After the addition is completed, the temperature is raised to 85° C. and refluxed for 4 hours, and then distilled under reduced pressure to obtain a hyperbranched polymer.

[0031] S2: 30 g of the hyperbranched polymer obtained in step S1 is dissolved in 200 ml of dimethyl sulfoxide, an organic solvent, and 1% of olefin phosphate is added. The temperature is raised to 60° C. and the mixture is sealed for reaction for 3 hours. After reduced pressure distillation, an ion-terminated hyperbranched polymer is obtained.

[0032] S3: Add 20 grams of PBT resin into a mixed solution of methanol and potassium carbonate, wherein the mass ratio of methanol to potassium carbonate is 10:3, and the total volume of the mixed solution is 200 milliliters. Heat to 90°C for alcoholysis reaction for 2 hours. After the reaction is completed, purify and remove the unreacted alcohol and the generated low-molecular alcohol, and then add a modifier prepared by propylene oxide and choline (the molar ratio of propylene oxide to choline is 2:1) to react with the alcoholysis product of the PBT resin. The amount of the modifier added is 5% of the weight of the PBT resin. The reaction temperature is 70°C and the time is 1.5 hours to obtain a multi-functional modified PBT resin.

[0033] S4: The ion-terminated hyperbranched polymer obtained in step S2 and the multifunctional modified PBT resin obtained in step S3 are added to a twin-screw extruder at a weight ratio of 1:4 for full melt blending, the screw speed of the extruder is 300 rpm, the melt temperature is set to 240°C, and the ultra-high viscosity PBT material is obtained by shearing, mixing, extruding, cooling, granulating, drying, and packaging. During the drying process, the material is dried at 60°C for 4 hours to ensure complete removal of moisture.

[0034] The intrinsic viscosity of the PBT material described in this embodiment is 1.45 dL / g.

[0035] Example 4, S1: Tris(4-aminophenyl)amine and trimethylolpropane trimethacrylate (TMPTMA) are respectively dissolved in an organic solvent, dimethyl sulfoxide. At 30°C and in a nitrogen atmosphere, trimethylolpropane trimethacrylate solution and crotonic acid are dropwise added to the tris(4-aminophenyl)amine solution, wherein the molar ratio of tris(4-aminophenyl)amine to trimethylolpropane trimethacrylate and crotonic acid is 1:1.5:1.5. After the addition is completed, the temperature is raised to 85°C and refluxed for 4 hours, and then distilled under reduced pressure to obtain a hyperbranched polymer.

[0036] S2: 30 g of the hyperbranched polymer obtained in step S1 is dissolved in 200 ml of dimethyl sulfoxide, an organic solvent, and 1% of olefin phosphate is added. The temperature is raised to 60° C. and the mixture is sealed for reaction for 3 hours. After reduced pressure distillation, an ion-terminated hyperbranched polymer is obtained.

[0037] S3: Add 20 grams of PBT resin into a mixed solution of butanol and potassium hydroxide, wherein the mass ratio of butanol to potassium hydroxide is 10:3, and the total volume of the mixed solution is 200 milliliters. Heat to 90°C for alcoholysis reaction for 2 hours. After the reaction is completed, purify and remove the unreacted alcohol and the generated low-molecular alcohol, and then add a modifier prepared by propylene oxide and choline (the molar ratio of propylene oxide to choline is 2:1) to react with the alcoholysis product of the PBT resin. The amount of the modifier added is 5% of the weight of the PBT resin. The reaction temperature is 70°C and the time is 1.5 hours to obtain a multi-functional modified PBT resin.

[0038] S4: The ion-terminated hyperbranched polymer obtained in step S2 and the multifunctional modified PBT resin obtained in step S3 are added to a twin-screw extruder at a weight ratio of 1:4 for full melt blending, the screw speed of the extruder is 300 rpm, the melt temperature is set to 240°C, and the ultra-high viscosity PBT material is obtained by shearing, mixing, extruding, cooling, granulating, drying, and packaging. During the drying process, the material is dried at 60°C for 4 hours to ensure complete removal of moisture.

[0039] The intrinsic viscosity of the PBT material described in this embodiment is 1.38 dL / g.

[0040] Comparative Example 1: The preparation method of the ultra-high viscosity PBT material in this comparative example has the same raw material composition and preparation steps as those in Example 1, except that in the preparation method of this comparative example, steps S1 and S2 are not performed. The intrinsic viscosity of the PBT material in this comparative example is 1.17 dL / g.

[0041] Comparative Example 2: The preparation method of the ultra-high viscosity PBT material in this comparative example has the same raw material composition and preparation steps as those in Example 1, except that step S2 is not performed in the preparation method of this comparative example. The intrinsic viscosity of the PBT material in this comparative example is 1.29 dL / g.

[0042] The ultra-high viscosity PBT materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to performance tests, and the performance results are shown in Table 1:

[0043] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention claimed.

Claims

1. A method for preparing an ultra-high viscosity PBT material, characterized in that: The preparation method comprises the following steps: S1: dissolving an aromatic homotriamine and trihydroxy triacrylate in an organic solvent respectively, and adding a trihydroxy triacrylate solution and an olefinic acid dropwise to the aromatic homotriamine solution at 15-30° C. in a nitrogen atmosphere. After the addition is completed, heating to 85-95° C. for reflux reaction, and then distilling under reduced pressure to obtain a hyperbranched polymer; S2: dissolving the hyperbranched polymer obtained in step S1 in an organic solvent, adding an ion capping agent, heating and sealing the reaction for a certain period of time, and performing reduced pressure distillation to obtain an ion-capped hyperbranched polymer; S3: adding the PBT resin to a mixed solution of a short-chain alcohol and a strong base, heating the solution to perform an alcoholysis reaction, purifying and removing the unreacted alcohol and the generated low-molecular alcohol after the reaction, adding a modifier prepared by propylene oxide and choline to react with the alcoholysis product of the PBT resin to obtain a multi-functional modified PBT resin; S4: adding the ion-terminated hyperbranched polymer obtained in step S2 and the multifunctional modified PBT resin obtained in step S3 into a twin-screw extruder for full melt blending, and then extruding, cooling, granulating, drying and packaging to obtain the ultra-high viscosity PBT material.

2. The method for preparing the ultra-high viscosity PBT material according to claim 1, characterized in that: The aromatic triamine is at least one of melem, melamine, 1,5,9-benzotriamine and tris(4-aminophenyl)amine.

3. The method for preparing the ultra-high viscosity PBT material according to claim 1, characterized in that: The trihydroxy triacrylate is at least one of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, and glycerol trihydroxypropyl ether triacrylate.

4. The method for preparing the ultra-high viscosity PBT material according to claim 1, characterized in that: The olefinic acid is at least one of acrylic acid, methacrylic acid and crotonic acid.

5. The method for preparing the ultra-high viscosity PBT material according to claim 1, characterized in that: The molar ratio of the aromatic triamine, trihydroxy triacrylate and olefinic acid is 1:1-1.5:1-1.

5.

6. The method for preparing the ultra-high viscosity PBT material according to claim 1, characterized in that: The ionic end-capping agent is at least one of olefin hydrochloride, olefin sulfonate or olefin phosphate.

7. The method for preparing the ultra-high viscosity PBT material according to claim 1, characterized in that: The short-chain alcohol is at least one of methanol, ethanol, isopropanol and butanol.

8. The method for preparing the ultra-high viscosity PBT material according to claim 1, characterized in that: The strong base is at least one of sodium hydroxide, potassium hydroxide and potassium carbonate.

9. An ultra-high viscosity PBT material, characterized in that: The PBT material is prepared by the method for preparing the ultra-high viscosity PBT material according to any one of claims 1 to 8.

10. The ultra-high viscosity PBT material according to claim 9, characterized in that: The intrinsic viscosity of the PBT material is 1.3-1.5 dL / g.